2020
DOI: 10.1108/inmr-08-2019-0096
|View full text |Cite
|
Sign up to set email alerts
|

How innovative climate leads to project success: the moderating role of gender and work culture

Abstract: Purpose In modern times, innovation is considered as a vital component of sustainable competitive advantage. The purpose of this paper is to identify how innovation at the individual level [innovative work behavior (IWB)] and at the organizational level [innovative organizational climate (IOC)] affects the chances of success of a particular project. Additionally, the moderating effect of gender and work culture on the relation between innovative climate and behavior is tested in the study. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…Eventually, knowledge-hiding behaviour that triggers down to employees results in poor IWB, which can adversely affect project success because practitioners emphasise on the importance of IWB among individual employees in determining organisational success (De Jong and Den Hartog, 2008). Another study evidenced that individual-level IWB can affect the chances of project success (Sarwar et al ., 2020). Hence, this study proposes that IWB acts as a mediator between knowledge-hiding behaviour and project success.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, knowledge-hiding behaviour that triggers down to employees results in poor IWB, which can adversely affect project success because practitioners emphasise on the importance of IWB among individual employees in determining organisational success (De Jong and Den Hartog, 2008). Another study evidenced that individual-level IWB can affect the chances of project success (Sarwar et al ., 2020). Hence, this study proposes that IWB acts as a mediator between knowledge-hiding behaviour and project success.…”
Section: Introductionmentioning
confidence: 99%
“…From researchers' view point, this may be due to increasing positive feelings among head nurses provided by good work climate and their feeling of compassion, reassurance, confidence, which motivates them to not only do their best but to innovate in their routine performance. This result was supported by Bos-Nehles and Veenendaal (11) they had stated that when the organization climate providing value, rewarding innovative ideas, and the work environment is focused on generating and championing new ideas, they will recreate with innovative behaviors.…”
Section: Answering the 3 Rd Research Question Concerning The Total Le...mentioning
confidence: 82%
“…The current study depended on previous literature which includes various studies proved the relation between organizational climate and innovative work behaviors such as; (11,12,13) . Regarding the relation between organizational climate, innovation and innovative work behaviors, number of studies handled this aspect and assured the relations among them such as; (14,15,16) .…”
Section: Conceptual Framework Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that inventiveness be treated as an independent variable (Vandavasi, Yepuru, Uen & McConville, 2020). Furthermore, it has been suggested that transformational leaders' subdimensions receive more attention because different antecedents may correlate with different aspects of leadership behaviours (Sarwar, Zahid, Imran & Anjum, 2020). There have been no studies on how the most creative and innovative people perceive them as having varying levels of importance (Vandavasi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%